Concept or Practice: Kajian Tentang Respon Kemampuan Kognitif Mahasiswa Pada Matakuliah Penganggaran - Miranti Puspaningtyas; Sulastri Sulastri (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The way a person receives knowledge has various kinds of responses according to their abilities. This research aims to develop an effective learning approach and the response of students' cognitive abilities in budgeting courses both in theory and practice. A quantitative approach is used as a type of Research and Development (R&D) methods on 102 accounting students who taking Budgeting Courses. Data were obtained from Accounting Students of the Faculty of Economics, UM, who were still taking budgeting courses and were given a questionnaire. The results of observations made in the budgeting course showed that the enthusiasm shown by students showed a good and enthusiastic attitude when explained by the lecturer about practical and theoretical. However, when the students were asked to do practice questions in the theory course, they had difficulty applying the theory to the problem. When online lectures, the conclusion is the use of appropriate learning methods and approaches and media will be simulate the response of students' cognitive abilities both theoretically and practically.